Pathomechanism of testicular inflammation in rat involves activation of proteinase activated receptor 2 - Iosub, Ioan Radu; Justus Liebig University Giessen (My University, 2006)
Mast cells are involved in early events crucial to inflammation and autoimmunedisease and their numbers increase in infertile testis. Recently, proteinaseactivated receptor-2 (PAR2), a G-protein coupled receptor important to injury responses, was shown to be activated by mast cell tryptase. To investigate whether mast cells and PAR2 are involved in the development and/oraggravation of testicular inflammation, we studied acute and chronicinflammatory models in the rat. Both testicular and systemic inflammatoryresponses can lead to impaired spermatogenesis, steroidogenesis and to maleinfertility. The rat experimental autoimmune orchitis (EAO) is thus far the beststudied model for immunological male factor infertility. In EAO, we detected asubstantial increase in the number of neutrophils, macrophages and mast cells,enlarged interstitial space, severe reduction and sloughing of the seminiferousepithelium and granuloma formation. Mast cells increased 10-fold in numbers,were more widely distributed and showed an increased degranulation rate.

In der Frühentwicklung von entzündlichen und autoimmunologischen Erkrankungen spielen Mastzellen eine essentielle Rolle. Ihre Anzahl ist auch im Hoden infertiler Männer erhöht. Testikuläre und systemische Entzündungen können zu eine Beeinträchtigung der Spermatogenese und Steroidogenese und damit zu Infertilität bei Männern führen. Kürzlich konnte gezeigt werden, dass der G-Protein gekoppelte Proteinase aktivierte Rezeptor-2 (PAR2), dem ein wichtige Funktion bei Wundheilungen zufällt, durch Mastzell-Tryptase aktiviert werden kann. In unserer Studie wurde eine mögliche Beteiligung von Mastzellen und PAR2 bei der Entstehung und Progression testikulärer Entzündungen mit Hilfe von Modellen akuter und chronischer Entzündungen in Ratten untersucht.
Pathomechanismus testikulärer Entzündungen bei Ratten ausgelöst durch Aktivierung von PAR2
Keywords: ddc:610